The pesantren: Politics of islamic and problematic education muslim identity - Fakhrurrazi, Fakhrurrazi; Indra P, I Made; Zainuddin, Yusran; Zulkarnaini, Zulkarnaini (Universitas Malikussaleh, 2021)
This program aims to discuss the politics of Islamic education and the problems of Muslim identity in Islamic boarding schools. The philosophy believed in the Islamic boarding school is based on Islam, and furthermore, the philosophy of education is based on the philosophical principles it adheres to. In the beginning, the main objective of the pesantren was to prepare students to deepen and master the science of religion (tafaqqahu fi al-din), the reproduction of ulama where the teaching of religious knowledge (transfer of Islamic knowledge), maintaining the Islamic tradition (maintenance of Islamic) tradition) and Islamic character building. Cottage The pesantren is a place of traditional education which has been very much felt by all elements, both society and government. Political education is an interdisciplinary study that integrates political science and education science, to see the dynamic relationship between various political issues and educational issues. To overcome the problem of Muslim identity, the dimensions mentioned above greatly affect Muslim identity because substantively, Islam is the same everywhere, namely the religion of Allah which was brought by the Prophet Muhammad as a guide for mankind. The emergence of various Islamic identities lately need not be responded to with excessive suspicion. Even the identity of Islam can become even more diverse when the typology of thought, understanding and practice of Islam is viewed from various perspectives both in the west and in the east.